2017
DOI: 10.3389/fpls.2017.01016
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Drought Stress Induces Increased Foliar Dimethylsulphoniopropionate (DMSP) Concentration and Isoprene Emission in Two Contrasting Ecotypes of Arundo donax

Abstract: The function of dimethylsulphoniopropionate (DMSP) in plants is unclear. It has been proposed as an antioxidant, osmolyte and overflow for excess energy under stress conditions. The formation of DMSP is part of the methionine (MET) pathway that is involved in plant stress responses. We used a new analytical approach to accurately quantify the changes in DMSP concentration that occurred in two ecotypes of the biomass crop Arundo donax subject to moderate drought stress under field conditions. The ecotypes of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 73 publications
(125 reference statements)
8
20
0
Order By: Relevance
“…) (Morfopoulos et al ) that, in turn, may confer oxidative and heat stress protection (Peñuelas et al , Loreto and Schnitzler ). These results are in line with those found by Ahrar et al () and Haworth et al (, ), which showed that isoprene emission from different genotypes of giant reed was stimulated by water stress.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…) (Morfopoulos et al ) that, in turn, may confer oxidative and heat stress protection (Peñuelas et al , Loreto and Schnitzler ). These results are in line with those found by Ahrar et al () and Haworth et al (, ), which showed that isoprene emission from different genotypes of giant reed was stimulated by water stress.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, the decrease in g s was accompanied by a decrease in P n (Fig. 1) in a typical hyperbolic relationship fashion confirming a strong diffusive limitation to P n under DR conditions (Nackley et al 2014, Haworth et al 2017a, 2017b. Consistently with biomass production, P n and g s decreased, respectively, by 30 and 59% with DR.…”
Section: Aboveground Biomass Yield Biometrical Growth and Leaf Physsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the δ 13 C values of leaf petiole sugars were higher than sugars from the leaf or branch sap (Table 1) in both well-watered control and drought-stressed plants, indicating a higher proportion of the heavier 13 C-isotope. The higher δ 13 C of sugars from the leaf petiole sap may reflect the impact of increased discrimination against sugars composed of the heavier isotope [51] during respiration or at other branch points of the metabolic pathways within the leaf, the methylerythritol pathway [52]. Discrimination in favour of sugars composed of the lighter 12 C-isotope will progressively enrich the remaining pool of photosynthetic sugars destined for export from the leaves to the other parts of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…A. donax leaves constitutively produce a large amount of isoprene (Velikova et al , 2016), which is known to be involved in mechanisms of protection against abiotic (Vickers et al , 2009) and biotic stresses (Loivamäki et al , 2008). However, there is no clear pattern in isoprene emission in response to abiotic stress in reeds, as isoprene emission increased in A. donax following drought (Haworth et al , 2017a), decreased in Phragmites australis (the common reed, and a close relative of Arundo) plants exposed to high P concentrations (Fares et al , 2006), and was unaltered in salt-stressed A. donax (Pollastri et al , 2018).…”
Section: Introductionmentioning
confidence: 99%